2020
DOI: 10.1038/s41598-020-78481-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel nerve transection and repair method in mice: histomorphometric analysis of nerves, blood vessels, and muscles with functional recovery

Abstract: Peripheral nerve transection is associated with permanent functional deficit even after advanced microsurgical repair. While it is difficult to investigate the reasons of poor functional outcomes of microsurgical repairs in humans, we developed a novel pre-clinical nerve transection method that allows reliable evaluation of nerve regeneration, neural angiogenesis, muscle atrophy, and functional recovery. Adult male C57BL/6 mice were randomly assigned to four different types of sciatic nerve transection: Simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…To assess the process of Wallerian degeneration more accurately, we detected the axon and myelin remained in the distal segment of transected sciatic nerve. In this way, the regenerating axons and myelin extending from the proximal nerve into the distal trunk, which occurs in most PNI models, could be avoided [ 36 , 60 ]. From the results of Western blots and immunofluorescence, we found that much more axonal and myelin fragments, as well as their proteins, remain in the cKO group which indicated RhoA conditional knockout in macrophages results in the delayed process of Wallerian degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the process of Wallerian degeneration more accurately, we detected the axon and myelin remained in the distal segment of transected sciatic nerve. In this way, the regenerating axons and myelin extending from the proximal nerve into the distal trunk, which occurs in most PNI models, could be avoided [ 36 , 60 ]. From the results of Western blots and immunofluorescence, we found that much more axonal and myelin fragments, as well as their proteins, remain in the cKO group which indicated RhoA conditional knockout in macrophages results in the delayed process of Wallerian degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Stretch is another common deformation of nerves, especially for transected nerves undergoing strong retraction due to the elastic endoneurium. [ 37 ] A tensile test was used to pull two nerves connected by adhesives to determine stretching adhesion forces. The DNNA showed a higher failure force and adhesion strength than HA‐Cat, but no significant difference was observed between HA–TU–Cat and DNNA (Figure 3C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Tiling and z-stack functions were used to image whole nerve. Maximum intensity projection was used to pull the data from all Z-stacks and represent it as a 2-D image [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%